Hydrothermal Synthesis and Crystal Structure of a Ni(II) Complex with Diacetyl Dihydrazone Ligand - Bi, Jian-Hong; Dong, Hua-Ze; Huang, Zi-Xian (Asian Journal of Chemistry, 2013)
A novel nickel(II) complex NiL3·(ClO4)2 (L = diacetyl dihydrazone) has been synthesized by hydrothermal method and characterized by IR spectra and single-crystal X-ray method. The crystal is trigonal, space P-3c1 with unit cell parameters: a = 9.5922(5) Å, b = 9.5922(5) Å, c = 15.1871(14) Å, a = 90º, b = 90º, g = 120º, V = 1210.16(14) Å3, Z = 2, Mr = 600.09, Dc = 1.647 Mg/cm3, μ = 1.087 mm-1, F(000) =624, T = 293(2) K, R = 0.0474, wR = 0.1276 for 8580 reflections with I > 2s(I).